Nucleotide sequence of the CytR regulatory gene of E. coli K-12. - Valentin-Hansen, P (1986)
We have determined the nucleotide sequence of the cytR gene, which codes for the Cyt repressor (CytR). The coding region consists of 1023 or 1029 bp. The subunits of CytR are thus predicted to consist of 341 or 343 residues. It is shown that the N-terminal segment of the polypeptide is structurally similar to the DNA-binding region of known DNA-binding proteins. In addition, there exists an exceptionally high amino acid sequence homology between CytR and the Gal repressor, indicating a common origin of evolution.